Musik Keroncong Sebagai Identitas dan Media Spiritualitas dalam Ibadah Gereja Kristen Muria Indonesia (GKMI) Brangkongan - Kurniawan Hidayat, Yosua; Krisno Utomo, Yunatan (STT Kristus Alfa Omega, 2025)
This study examines the existence and arrangement of keroncong music in worship at Gereja Kristen Muria Indonesia (GKMI) Brangkongan during the period 2024-2025. The aim is to understand the extent to which keroncong music exists and how the arrangement is applied in the context of worship in the church. Specifically, this study aims to analyze the arrangement and existence of keroncong music at GKMI Brangkongan with a focus on keroncong music accompaniment. In addition, this study also aims to evaluate the skills of keroncong musicians and understand how keroncong music exists in GKMI Brangkongan.The method used in this study is qualitative, where researchers conduct direct observations in the field, and use recording, photography, and interviews as data collection methods. The data obtained are then analyzed to draw conclusions regarding the existence and presence of keroncong music. The results of the study indicate that this analysis is very important in helping keroncong players improve their skills and understand the existence of keroncong music at GKMI Brangkongan. This study provides a better understanding of the needs and understanding of the congregation regarding the existence of keroncong music and serves as a benchmark for future development.